A anta de Monte Serves (Vialonga, Vila Franca de Xira, Lisboa): arquitectura, cronologia e integração sócio‑cultural de um pequeno sepulcro megalítico - Andrade, Marco António (2024)
The dolmen of Monte Serves, located in Vila Franca de Xira (Lisbon peninsula), corresponds to a small megalithic tomb with a trapezoidal plan built using limestone slabs. It was identified in 1972 by Octávio da Veiga Ferreira, being excavated that same year under the direction of Christopher Thomas North. In 2014, within the scope of the project MEGAGEO – Moving Megaliths in the Neolithic, this monument was the subject of new archaeological works, directed by Rui Boaventura and João Luís Cardoso, intending to define its specific architecture and the respective construction sequences, mainly regarding the Tumulus and the Atrium areas. Despite the practical absence of votive materials, it was possible to collect human osteological samples, thus allowing to perform radiocarbon dating – whose average result places at least one use episode of this tomb (not necessarily its first) in the transition from the first to the second quarter of the 3rd millennium BCE (median probability: 2706 cal BCE 2σ; mean: 2715 cal BCE 2σ). Indeed, this result differs greatly from the chronological framework established for this type of small tombs in Southwestern Iberia (mid‑4th millennium BCE), but is close to the chronology (relative and absolute) documented in the contiguous funerary contexts of Casal do Penedo and Verdelha dos Ruivos, as well as in the settlements of Moita da Ladra and Pedreira do Casal do Penedo, culturally included in the typical Chalcolithic of Portuguese Estremadura. This paper thus intends to present the results obtained with the excavation of this small tomb, in terms of its architecture and chronology, framing it within the socio‑cultural dynamics documented in Lower Extremadura during the Neolithic and Chalcolithic, mainly regarding the origin and development of the megalithic phenomenon.